ANALISIS DAN PERANCANGAN APLIKASI PERSEDIAAN PADA CV. FAJAR KHATULISTIWA MOTOR PONTIANAK - Susanti Margaretha Kuway (STMIK PONTIANAK, 2011)
Abstracts : On this paper, we conducted research on the CV. Fajar Khatulistiwa Pontianak where there are obstacles in the sales of goods such as difficulty in finding goods data, customer data, the records are repeated due to recording errors or missing files. Besides the old reporting process because the data must be re-examined and cannot be generated immediately, it is this which causes slow reports must be submitted to the leadership. The method used in this research is descriptive method and data collection techniques using interviews, observation and documentary studies. System development methodology used is Data Flow Diagram, Data Dictionary, Normalization, Databases and Tables Specification Entity Relationship Diagram. The results of this proposed prototype design using Visual Basic 6.0 programming language which can assist companies in dealing with inventory. Moreover, it can facilitate the sale and purchase of data storage, data storage sales returns and purchase and storage of data in or out goods. Keywords : Sales Information System, Protoype, System Development Methodology, Microsoft Visual Basic 6.0